An Effective Relay Node Selection Technique for Energy Efficient WSN-Assisted IoT - Shukla, Anurag; Tripathi, Sarsij (Wireless personal communications, 2020)
The internet of things (IoT) is one of the emerging network paradigms that are reducing the distance between the physical and cyber world. In wireless sensor Network (WSN)-assisted IoT, hundreds to thousands of sensor nodes are deployed at a large scale, which in turn increases the complexity. Therefore, the issues and challenges of such network differ from WSN. The sensor nodes are an important component of WSN-Assisted IoT network running on limited and non-rechargeable energy resource. So, developing robust and energy-efficient routing protocol is a challenging task to prolong the network lifetime. In contrast to the state-of-the-art techniques this paper introduces: (1) a hierarchical cluster framework for network deployment; (2) an effective Relay Node (RN) selection scheme by considering the following parameters: node density in the cluster, shortest distance node selection as a RN, RN communication range as threshold distance for next RN selection; (3) an efficient routing algorithm to meet the requirement of proposed model. The proposed protocol has been compared with standard WSN routing protocols, viz., LEACH, MOD-LEACH, ME-CBCCP, EESAA, TDEEC, DEEC, and SEP. By extensive simulation for various network parameters, the proposed effective relay node selection for energy efficient consumption protocol found to be more effective in terms of network lifetime, energy consumption and supports scalability.